Variability in Prebiotic Carbohydrates in Different Market Classes of Chickpea, Common Bean, and Lentil Collected From the American Local Market - Siva, Niroshan; Thavarajah, Pushparajah; Kumar, Shiv; Thavarajah, Dil (Frontiers in Nutrition, 2019)
Pulse crops such as lentil, common bean, and chickpea are rich in protein, low digestible carbohydrates, and range of micronutrients. The detailed information of low digestible carbohydrates also known as “prebiotic carbohydrate” profiles of commonly consumed pulse market classes and their impact on human health are yet to be studied. The objective of this study was to determine the profiles of prebiotic carbohydrates in two commonly consumed lentil market classes, seven common bean market classes, and two chickpea market classes. After removing fat and protein, total carbohydrates averaged 51/100 g for lentil, 53/100 g for common bean, and 54/100 g for chickpea. Among the portion of total carbohydrates, lentil showed 12/100 g of prebiotic carbohydrates (sugar alcohols, raffinose family oligosaccharides, fructooligosaccharides, hemicellulose, cellulose, and resistant starch), 15/100 g in common bean, and 12/100 g in chickpea. Prebiotic carbohydrate concentrations within the market classes for each crop were significantly different (P < 0.05). In conclusion, these three pulses are rich in prebiotic carbohydrates, and considering the variation in these concentrations in the present materials, it is possible to breed appropriate market classes of pulses with high levels of prebiotic carbohydrates.